2013
DOI: 10.4103/2141-9248.117949
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition intervention program and childhood malnutrition: A comparative study of two rural riverine communities in Bayelsa State, Nigeria

Abstract: Background:The prevalence of malnutrition is high in the Niger delta region of Nigeria, in spite of the region's oil wealth and nutrition intervention programs have been found to be effective in similar circumstance.Aim:This study is to assess the nutrition intervention program, implemented by UNICEF in some rural communities of Bayelsa State, one of the six States in the Niger delta region of Nigeria.Subjects and Methods:The study was carried out in 2009 in Toruorua and Gbaranbiri, two rural riverine communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In national studies conducted in 1995, ANISE1 and ANISE2 also reported similar results [585960]. In the studies conducted in other parts of the world, the differences between these indices between girls and boys are not statistically significant and are consistent with the present study [40414243444546]. UNICEF reports show that the prevalence of underweight between boys and girls is similar in developing countries [61].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In national studies conducted in 1995, ANISE1 and ANISE2 also reported similar results [585960]. In the studies conducted in other parts of the world, the differences between these indices between girls and boys are not statistically significant and are consistent with the present study [40414243444546]. UNICEF reports show that the prevalence of underweight between boys and girls is similar in developing countries [61].…”
Section: Discussionsupporting
confidence: 87%
“…For example, a meta-analytical study in 32 countries from the north, south, west and sub-Saharan Africa showed that children under the age of five were 25% to 36.4% underweight, 36.6% to 57.7% short, and 6.2% to 18% slim [40]. The prevalence of underweight in Nigeria was 17.1%, 24.8% and 20%, respectively [41]. A meta-analysis in Ethiopia showed that children under the age of five had 33% underweight, 40% short stature, and 19% slimness [42].…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions led to the introduction of nutrition policies, plans, and interventions with the aim of improving caregivers' knowledge of appropriate foods and feeding practices for their young children. The interventions include protecting and advancing food and nutrition security in Yobe State; efforts to positively transform nutrition in northern Nigeria; improving maternal, newborn, and child nutrition in northern Nigeria; national policies on food and nutrition in Nigeria; National Plan of Action on Food and Nutrition (NPAN) in Nigeria; National Strategic Plan of Action for Nutrition (2014-2019); UNICEF implemented nutrition intervention programs; 2017 Nigeria Nutrition in Emergency Sector Response Plan; and 2018 Zero Hunger Initiative [9,[16][17][18][19][20][21][22][23][24][25][26]. More so, food supplementation, food fortification, and biofortification of staple crops have been employed to address nutrient deficiencies among children and mothers in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, breastfeeding is a widespread practice in Nigeria with 97.1% children aged 0-23 months ever breastfed, but only a few mothers breastfeed exclusively (NNHS, 2018). Women are encouraged to continue breastfeeding alongside complementary food until the child is two years (Sawyer et al, 2013;WHO, 2013). Although mothers are not favourably inclined to the practice, it is not new as it existed in traditional Ugep society where women breastfed beyond two years for contraceptive advantage (Obono, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because malnutrition is high among under-two children in Nigeria (NNHS, 2018), nutrition information, education and intervention is important to reduce infant mortality and malnutrition (Sawyer, Ordinioha & Abuwa, 2013). Implementation of the information would lay a healthy and disease-free foundation for children.…”
Section: Literature Reviewmentioning
confidence: 99%